1998
DOI: 10.1016/s0886-3350(98)80283-6
|View full text |Cite
|
Sign up to set email alerts
|

Excimer laser phototherapeutic keratectomy for recurrent corneal erosion

Abstract: Excimer laser PRK appears to be a safe and effective treatment for recurrent erosions of the cornea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 14 publications
3
24
1
Order By: Relevance
“…A literature review was completed to look at long term follow-up of PTK for RCES. In this study, with a mean follow-up of 12 ± 1.52 years (range, 10 to 14 years), we report the longest follow-up after PTK for RCES compared to other studies (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) . Overall our results may contribute to establish the very long term success of this technique.…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…A literature review was completed to look at long term follow-up of PTK for RCES. In this study, with a mean follow-up of 12 ± 1.52 years (range, 10 to 14 years), we report the longest follow-up after PTK for RCES compared to other studies (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) . Overall our results may contribute to establish the very long term success of this technique.…”
Section: Discussionmentioning
confidence: 49%
“…Excimer laser, with its facility to ablate corneal tissue with extreme precision and minimal adjacent tissue damage has been a useful tool in the management of RCES (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) . Studies have shown that partial ablation of Bowman's layer gives a smooth bed for migrating epithelium, and results in new hemidesmosomal adhesion complexes (20,21) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations